The trend of homicides in South Kerala from 2002-2016: A retrospective forensic autopsy-based study - Nikhil Dileeph; S Sharija; Antony Stanley; K Valsala; S S Sujisha; Nikita Prabhakaran (Wolters Kluwer Medknow Publications, 2021)
Aims: The aim was to analyze the homicide pattern in South Kerala from autopsies conducted between 2002 and 2016. Objectives: Exploring the age and gender distribution of death due to homicide, the type and distribution of injuries according to the region of the body, and trends of homicide. We also tried to study the pattern of defense wounds in homicidal cases and characteristics in dyadic deaths (homicide-suicide). Materials and Methods: It was a retrospective descriptive study. The setting was the Department of Forensic Medicine, State Medico-Legal Institute, Government Medical College (GMC), Thiruvananthapuram. All cases of autopsies with an alleged history of homicide, between 2002 and 2016, done at Mortuary of GMC, Thiruvananthapuram, were included in the study. Records of all cases of an alleged history of homicide from January 1, 2002 to December 31, 2016 were perused. Results: 957 cases were analyzed. The annual incidence of homicide is declining after 2012. Young adult males (31-40 years) are the most common group involved (24.97%). Head injury was the most common cause of death (43.68%). The head was the most common area to be affected in fatal blunt force injuries (49%) while the chest was involved commonly in fatal sharp force injuries (36%). Females were more often the homicide victims in murder-suicides. Husband-wife and father-child combination was the most common pairs in dyadic deaths. Conclusion: The characteristics which were associated with the homicides were generally in agreement with the existing forensic literature. The findings encourage examining the motives of homicide and potential sociocultural factors affecting the victims and possibly the assailants. We also found that the murder-suicide cases differed from the homicides requiring a separate domain of understanding and subsequent investigations.